Shared Pathogenesis in Depression and Cancer Depicting the Anti-cancer Properties of Anti-depressants - Faye, Abhijeet (Asian Pacific Journal of Cancer Biology, 2021)
Pathogenesis of depression is similar to that of cancer in many aspects. Important mechanisms include effects on hypothalamo-pituitary-adrenal axis (HPA axis), functions of prostaglandins, inflammatory markers and cellular immunity. Anti-depressants must have the actions through above mentioned mechanisms when used to treat depression. Literature has mentioned the effects of various anti-depressant agents in reversing or modifying the pathogenic changes that occur in cancer too. It’s worth exploring the anti-cancer properties of anti-depressants and utilize those for the treatment of cancer whenever used for treating associated depression or other psychiatric conditions. Long term studies are needed to prove this less researched aspect of antidepressants.